An analysis of zero-trust architecture and its cost-effectiveness for organizational security. Issue 122 (November 2022) - Adahman, Zillah; Malik, Asad Waqar; Anwar, Zahid
Abstract: Zero Trust Architecture (ZTA) is a 'Never Trust, Always Verify' concept to improve cybersecurity by eliminating trust and validating network requests continuously. Zero Trust Architecture (ZTA) is here to replace Virtual Private Networks (VPNs) and provide solitary access to applications and data. The growth of ZTA has spiked over the years, but organizations are reluctant to invest in the security approach. Previous research studies cover ways to implement or migrate to ZTA, its significance, and challenges but provide limited information on available tools, prices, and the success rate of ZTA. Organizations lack information on the quantitative evaluations of ZTA benefits and drawbacks. An in-depth evaluation of ZTA to help security researchers better understand the costs and benefits of employing this new technology as a defence against cyber attacks is provided in this work. Results show that the implementation of ZTA causes a reduction of 684K on average in risk impact over a span of four years for small to medium sized organizations and enterprise-level organizations.